Perangkat Lunak Edukasi Berbahasa Jepang dengan Pendekatan UI Framework Menggunakan React Native - Apriyo Fadli; Rahayu Amalia (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2023)
The rapid development of technology has brought about changes in the field of education, one of which is the ease of accessing information. Thanks to this convenience, foreign cultures and even their languages also enter the country. The incoming language will sound and look foreign to us. To understand it, of course, we have to learn the language. A survey conducted by The Japan Foundation proves that interest in learning Japanese in Indonesia is still high. However, it is not easy to learn Japanese because of the differences in the alphabets used. This difference in letters is sometimes the biggest obstacle for someone in learning Japanese. To overcome this problem, the author wants to create an application to introduce Japanese letters according to the concept of user interface. This application will also be made using the react native framework and the waterfall method, whose stages consist of display design, prototype, coding, testing, and maintenance. The result of this research is an application to introduce Japanese letters that provides material about Japanese letters and quiz questions.